الحقوق العينية التبعية المترتبة على السفينة دراسة مقارنة: دراسة مقارنة - مشيري حسن مكي (Journal of Legal Sciences, 2019)
There is no doubt that the exploitation of the ship in navigation requires large expenditures make their owners or processors in constant need to borrow from third parties for the purpose of maintenance of the vessel or processing with supplies and fuel or by providing them with tasks and equipment necessary for the exploitation of ship , and since all the money the debtor is general guarantee to meet its debts , but the creditor You may not get the full right, as other creditors could challenge him where the money is shared on all creditors of the debtor, the existence of public security does not distinguish between the creditors, the debtor may also sometimes smuggled money creditor is not able to get right. In order to this , For this legislator has decided on the rights of creditors of the owners of the ship through insurance-kind accessory that enables them to get right before other creditors and ensure the fulfillment of their rights first before ordinary creditors, he decided to privilege and the mortgage the ship for the benefit of creditors bonded, so to them in case of non-fulfillment debtor religion the right to progress to meet their debts before other ordinary creditors the right to follow the ship in any hand be, has provided the legislator legal means to maintain the rights of creditors of the owner or equipped ship and to protect them from the debtor’s business and smuggling ship to out of state by filing booking the ship, such as privilege and the mortgage the ship Executive on the ship. In this paper, entitled rights in rem arising from the ship divided the subject into two parts in the first I study maritime privilege rights on the ship legal implications between contractors and the order of degrees of, privilege rights and how the expiration of the, privilege rights and in the second section dealt with the right of mortgage on the ship and the legal implications between contractors and the expiration of the mortgage Marine and Conclusion In the end, with some of the Recommendation.